Enhanced anti-lymphoma activity of CAR19-iNKT cells underpinned by dual CD19 and CD1d targeting - Rotolo,A; Caputo,VS; Holubova,M; Baxan,N; Dubois,O; Chaudhry,MS; Xiao,X; Goudevenou,K; Pitcher,DS; Petevi,K; Kachramanoglou,C; Iles,S; et al. (Cancer Cell, 2018)
Chimeric antigen receptor anti-CD19 (CAR19)-T cell immunotherapy-induced clinical remissions in CD19+ B cell lymphomas are often short lived. We tested whether CAR19-engineering of the CD1d-restricted invariant natural killer T (iNKT) cells would result in enhanced anti-lymphoma activity. CAR19-iNKT cells co-operatively activated by CD1d- and CAR19-CD19-dependent interactions are more effective than CAR19-T cells against CD1d-expressing lymphomas in vitro and in vivo. The swifter in vivo anti-lymphoma activity of CAR19-iNKT cells and their enhanced ability to eradicate brain lymphomas underpinned an improved tumor-free and overall survival. CD1D transcriptional de-repression by all-trans retinoic acid results in further enhanced cytotoxicity of CAR19-iNKT cells against CD19+ chronic lymphocytic leukemia cells. Thus, iNKT cells are a highly efficient platform for CAR-based immunotherapy of lymphomas and possibly other CD1d-expressing cancers.